Revitalisasi Bangunan Heritage Menjadi Galeri dan Restoran di Surabaya Dengan Konsep Oud voor Millenial - Yosafat Satrio Pinandito; Diana Thamrin; Linggajaya Suryanata (Intra, 2019)
Cultural heritage buildings are buildings that have historical values that are associated with past historical events and are at least 50 years old. At present, many heritage buildings have undergone devaluation and are under the status of abandoned buildings due to the lack of maintenance. This interior revitalization design aims to reuse an abandoned heritage building in order to preserve it as a historical heritage. Through adaptive reuse of the building as a restaurant and gallery, the design aims to attract millennials so that the community, especially the millennial generation, can better appreciate the cultural heritage building not only as a place for dining and recreation, but also as a building with historical value. The method used is Design Thinking consisting of six stages: Discover, Observe, Ideate, Prototype, Test and Implement, with reports, design drawings and models as the design targets. The result of this thesis is a revitalization design of a heritage building with the concept of Vintage Millennial that adapts the atmosphere and facilities to the lifestyle of the Millennial generation without eliminating the Vintage elements of the heritage building.